Labor market participation and depression during the COVID-19 pandemic among young adults (18 to 30 years): A nationally representative study in France - Maria Melchior; Aline-Marie Florence; Camille Davisse-Paturet; Bruno Falissard; Bruno Falissard; Cédric Galéra; Jean-Baptiste Hazo; Cécile Vuillermoz; Josiane Warszawski; Josiane Warszawski; Fallou Dione; Alexandra Rouquette; et al. (Frontiers Media S.A., 2022)
ObjectiveTo examine the relationship between young adults' labor force participation and depression in the context of the COVID-19 pandemic.Design, setting, participantsData come from the nationally-representative EPICOV cohort study set up in France, and were collected in 2020 and 2021 (3 waves of online or telephone interviews: 02/05/2020-12/06/2020; 26/10/2020-14/12/2020; 24/06/2021-09/08/2021) among 2,217 participants aged 18-30 years. Participants with prior mental health disorder (n = 50) were excluded from the statistical analyses.ResultsUsing Generalized Estimating Equation (GEE) models controlled for participants' socio-demographic and health characteristics and weighted to be nationally-representative, we found that compared to young adults who were employed, those who were studying or unemployed were significantly more likely to experience depression assessed using the PHQ-9 (multivariable ORs, respectively: OR: 1.29, 95% CI 1.05-1.60 and OR: 1.50, 1.13-1.99). Stratifying the analyses by age, we observed that unemployment was more strongly associated with depression among participants 25-30 years than among those who were 18-24 years (multivariable ORs, respectively, 1.78, 95% CI 1.17-2.71 and 1.41, 95% CI 0.96-2.09). Being out of the labor force was, to the contrary, more significantly associated with depression among participants 18-24 years (multivariable OR: 1.71, 95% CI 1.04-2.82, vs. 1.00, 95% CI 0.53-1.87 among participants 25-30 years). Stratifying the analyses by sex, we found no significant differences in the relationships between labor market characteristics and depression (compared to participants who were employed, multivariable ORs associated with being a student: men: 1.33, 95% CI 1.01-1.76; women: 1.19, 95% CI 0.85-1.67, multivariable ORs associated with being unemployed: men: 1.60, 95% CI 1.04-2.45; women: 1.47, 95% CI 1.01-2.15).Conclusions and relevanceOur study shows that in addition to students, young adults who are unemployed also experience elevated levels of depression in the context of the COVID-19 pandemic. These two groups should be the focus of specific attention in terms of prevention and mental health treatment. Supporting employment could also be a propitious way of reducing the burden of the COVID-19 pandemic on the mental health of young adults.